Analisis Implementasi Pembelajaran Outing Class pada Mata Pelajaran PKn di SMA Plus Al-Azhar Medan - Sapta Kesuma; Tampilen Kaban (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This study aims to describe the inculcation of the values of archipelago insight that is integrated into Civics learning through Civics class outing activities at SMA Plus AL-Azhar Medan. The type of research used is descriptive qualitative research, namely research that is fundamental in nature and aims to describe or describe existing events or problems. The results showed that Civics class outing activities integrated into Civics learning aimed to foster and develop students to become good citizens, in addition to Civics learning to understand and be able to carry out their rights and obligations honestly and democratically in their lives as educated citizens. This is a very basic thing in Civics lessons that teach tolerance, tolerance and being able to respect each other. The form of outing class learning is in the form of community activities such as mutual cooperation around the school to get to know the archipelago's insights in social life.